Ethnography after antiquity : foreign lands and peoples in Byzantine literature - Kaldellis, Anthony (Empire and after., 2013)
This explores the modes and motivations of Byzantine ethnographic writing, shedding new light on how Byzantines distinguished themselves from foreign cultures.